A Bispecific Antibody to Link a TRAIL-Based Antitumor Approach to Immunotherapy - Satta, Alessandro; Grazia, Giulia; Caroli, Francesco; Frigerio, Barbara; Di Nicola, Massimo; Raspagliesi, Francesco; Mezzanzanica, Delia; Zaffaroni, Nadia; Gianni, Alessandro Massimo; Anichini, Andrea; Figini, Mariangela (Frontiers in Immunology, 2019)
T-cell-based immunotherapy strategies have profoundly improved the clinical management of several solid tumors and hematological malignancies. A recently developed and promising immunotherapy approach is to redirect polyclonal MHC-unrestricted T lymphocytes towards cancer cells by bispecific antibodies (bsAbs) that engage the CD3 complex and a tumor-associated antigen (TAA). The TNF-related apoptosis-inducing ligand receptor 2 (TRAIL-R2) is an attractive immunotherapy target, frequently expressed by neoplastic cells, that we decided to exploit as a TAA. We found that a TRAIL-R2xCD3 bsAb efficiently activates T cells and specifically redirect their cytotoxicity against cancer cells of different origins in vitro, thereby demonstrating its potential as a pan-carcinoma reagent. Moreover, to mimic in vivo conditions, we assessed its ability to retarget T-cell activity in an ex vivo model of ovarian cancer patients’ ascitic fluids containing both effector and target cells – albeit with a suboptimal effector-to-target ratio – with remarkable results.